2004
DOI: 10.1074/jbc.m313045200
|View full text |Cite
|
Sign up to set email alerts
|

Functional TIM10 Chaperone Assembly Is Redox-regulated in Vivo

Abstract: The TIM10 chaperone facilitates the insertion of hydrophobic proteins at the mitochondrial inner membrane. Here we report the novel molecular mechanism of TIM10 assembly. This process crucially depends on oxidative folding in mitochondria and involves: (i) import of the subunits in a Cys-reduced and unfolded state; (ii) folding to an assembly-competent structure maintained by intramolecular disulfide bonding of their four conserved cysteines; and (iii) assembly of the oxidized zinc-devoid subunits to the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
134
1
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 112 publications
(151 citation statements)
references
References 32 publications
8
134
1
8
Order By: Relevance
“…Mutation of the fourth cysteine residue in DDP1 (the human homologue of Tim8) affects the folding of the Tim8 protein and Tim8-Tim13 assembly (20,21). We have recently shown that the TIM10 complex is only formed between oxidized Tim 9 and Tim10 and that zinc can bind only to the fully reduced state without promoting complex formation (44). The combined data so far demonstrate the presence of an intimate relationship between, on one hand, the structure integrity, oxidation, and metal chelation states involving cysteine residues and, on the other, the formation of functional Tim9/ Tim10 complexes.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Mutation of the fourth cysteine residue in DDP1 (the human homologue of Tim8) affects the folding of the Tim8 protein and Tim8-Tim13 assembly (20,21). We have recently shown that the TIM10 complex is only formed between oxidized Tim 9 and Tim10 and that zinc can bind only to the fully reduced state without promoting complex formation (44). The combined data so far demonstrate the presence of an intimate relationship between, on one hand, the structure integrity, oxidation, and metal chelation states involving cysteine residues and, on the other, the formation of functional Tim9/ Tim10 complexes.…”
mentioning
confidence: 83%
“…Also, these experimental data provide a structural basis to a model for the redox-regulated multi-step mechanism of biogenesis and assembly of the TIM10 complex that we first postulated based on a combination of site-directed mutagenesis and functional studies (19,44). The major stages in this pathway are as follows: stage 1, the individual subunits Tim9 and Tim10 are maintained in an unfolded structure in the cytosol; and stage 2, the subunits are imported in a reduced state, which is assembly-incompetent.…”
Section: Discussionmentioning
confidence: 99%
“…Although not directly shown so far, this suggests a transfer of disulfide bonds from Mia40p to the interacting IMS proteins. The generation of intramolecular disulfide bonds has been proposed to trigger folding of substrates and thereby trapping of imported substrates in the IMS (26,27). Two redox forms of Mia40p have been detected in mitochondria, an oxidized and a reduced form.…”
mentioning
confidence: 94%
“…AMS Assays-At various time points, protein aliquots were removed from reaction solutions and added to nonreducing gel sample buffer containing excess amount of AMS (10 mM) for 30 min in the dark at room temperature as described before (26). AMS interacts with free thiols of reduced proteins covalently, but not disulfide bonds.…”
Section: Methodsmentioning
confidence: 99%